Associação entre concentração sérica de vitamina D e alterações da massa muscular esquelética em pacientes com doenças inflamatórias intestinais - Gondo, Fernanda Futino [UNESP] (2015)
Background: Changes in skeletal muscle mass and vitamin D deficiency have been frequently reported in the literature in patients with inflammatory bowel disease. However, the association between vitamin D and muscle changes in patients with inflammatory bowel diaseases is unclear. This study aimed to verify if changes in skeletal muscle mass are explained by nutritional status of vitamin D in patients with inflammatory bowel diseases. Methods: This observational study assessed 73 outpatients with Crohn's Disease and Ulcerative Colitis from Botucatu Medical School, Brazil, who have confirmed the diagnosis of their disease trough the clinical, endoscopic and histological parameters. Whole body and regional body composition was obtained by dual-energy X-ray absorptiometry. Criteria of European Working Group on Sarcopenia in Older People were used to define sarcopenia. Peripheral blood samples were obtained for measurements of hemoglobin, hematocrit, erythrocyte sedimentation rate, C-reactive protein, albumin, and serum 25-hydroxyvitamin D (25(OH)D). The 6-minute walk test was performed for evaluation of physical capacity, based on the guidelines established by the American Thoracic Society (2002). Grip strength of the subject's non-dominant hand was assessed with a hydraulic hand dynamometer, which measures isometric grip force. The International Physical Activity Questionnaire was used to evaluate the physical activity. The nutritional status of vitamin D was assessed by 24hour dietary recall and sun exposure questionnaire. All participants were asked about their alcohol intake and smoking. Results were expressed as mean ± SD or median with quartile 1 and quartile 3 ranges or percentage. We used the Fisher exact test for the associations between categorical variables, the Student t-test or Mann-Whitney test for differences between patients with sarcopenia or not and Multiple Logistic Regression. We adopted a significance level of 5% ...